EVALUASI PELAKSANAAN KEGIATAN OUTBREAK RESPONSE IMMUNIZATION (ORI) DIFTERI DI PUSKESMAS MIJEN KOTA SEMARANG TAHUN 2018 - Suci Aull Radian; Chriswardani Suryawati; Sutopo Patria Jati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Outbreak Response Immunization (ORI) is an activity carried out as an effort to overcome the outbreak of Diphtheria. Mijen Primary Health Center is one of the health centers in Semarang that organizes ORI activities because the discovery of a positive diphtheria case. Mijen Primary Health Center has decreased coverage in the second stage of ORI with a gap of 8.3%. The research objective is to evaluate the implementation of ORI activities in Mijen District by assessing the variables of surveillance, diagnosis, clinical management, supervision and assessment, infection control, and reporting. The research method uses qualitative research with a descriptive approach. This study interviewed 10 informants. The results showed that the implementation of ORI was able to reduce the rate of transmission and death from diphtheria. But the implementation of ORI still leaves a risk factor due to a decrease in ORI coverage which will result in an immunity gap. In addition, there is a large gap in setting targets for activities that are only carried out in an area of 3 RT in 3 villages, while according to the technical guidelines for the implementation of ORI, ORI should be at least one villages and one sub-district where cases are found. Target reduction due to limited resources and vaccine availability and vaccine logistics. Decrease in coverage is influenced by there are still people who do not believe that there is a case of diphtheria because the suspect claimed to be negative diphtheria. Counseling is also not maximal because most of the participants are cadres. Suggestions can be given to the Mijen health center is providing clear information to the public regarding the presence of diphtheria cases, increasing the intensity of counseling, reviewing the ORI target setting, Using PPE while working, and providing timely reports to the City Health Office.